2017
DOI: 10.1007/s00467-017-3627-2
|View full text |Cite|
|
Sign up to set email alerts
|

Viral load of EBV DNAemia is a predictor of EBV-related post-transplant lymphoproliferative disorders in pediatric renal transplant recipients

Abstract: A high PCR EBV viral load is correlated with the probability of developing PTLD. The definition of a reliable marker is essential to identify patients more at risk of PTLD and to personalize the clinical approach to the single patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 30 publications
2
54
1
1
Order By: Relevance
“…The role of EBV in the pathogenesis of PTLD is well documented; however, EBV-DNA load was not associated with true positive FDG-PET/CT results in our study [26]. EBV monitoring is a common clinical practice for early PTLD detection and various studies have advocated its importance as a predictor of PTLD development [3,[27][28][29][30][31]. Nonetheless, EBV-DNA load does not seem to affect the detection performance of FDG-PET/CT.…”
Section: Current Guidelines From the British Committee For Standards contrasting
confidence: 51%
“…The role of EBV in the pathogenesis of PTLD is well documented; however, EBV-DNA load was not associated with true positive FDG-PET/CT results in our study [26]. EBV monitoring is a common clinical practice for early PTLD detection and various studies have advocated its importance as a predictor of PTLD development [3,[27][28][29][30][31]. Nonetheless, EBV-DNA load does not seem to affect the detection performance of FDG-PET/CT.…”
Section: Current Guidelines From the British Committee For Standards contrasting
confidence: 51%
“…Approximately 5 × 10 5 copies/mL of EBV DNA was detected in our patients with EBV disease. Colombini et al have reported that the mean maximum EBV viral load was 3.4 × 10 8 copies/mL in paediatric renal recipients who tested positive for EBV and 1.9 × 10 7 copies/mL in patients who tested negative for EBV . In another study, EBV viral load at diagnosis was 2.5 × 10 4 copies/mL in the primary EBV infection group and 600 copies/mL in the EBV reactivation group .…”
Section: Discussionmentioning
confidence: 98%
“…Indeed, they consider PTLD histopathology independently of time of onset since transplantation . They separate disease into 1/plasma cell hyperplasia, which corresponds to early PTLD with exuberant lymphoid proliferation and preservation of normal tissue architecture despite the presence of a mass effect (such as enlarged lymph nodes, tonsils, adenoid hypertrophy), 2/non‐early PTLD with polymorphic PTLD (polyclonal or monoclonal), and monomorphic PTLD, in which the normal architecture of the involved tissue is partially or completely destroyed.…”
Section: Introductionmentioning
confidence: 99%